Tuning Energy Landscapes: Sequential Uphill and Downhill Pathways for Tetrasubstituted Carbon Construction - Sohtome, Yoshihiro; Sodeoka, Mikiko (Synlett, 2025)
The construction of vicinal tetrasubstituted carbon centers remains a synthetic challenge, mainly due to the reversible and endergonic nature of the C–C bond-forming process. Unlike exergonic transformations, strategies for overcoming the energetic penalty of uphill processes under thermal conditions have received comparatively little attention. Here, we report our experimental and computational studies on catalytic aerobic carbooxygenation, illuminating how the strategic balance between uphill and downhill energy profiles can be harnessed to construct vicinal tetrasubstituted carbon centers.
Keywords: Endergonic reactions; Tetrasubstituted carbon centers; Diastereoconvergency; Radicals; Molecular oxygen; Density functional calculation; Copper catalysis